Fungal exposure in agricultural environments: a review - Sousa, Pedro (2020)
Fungi can be easily found in agriculture environments due to the good growing conditions that are provided by the raw materials present in this environment and for its storage temperatures. Due to the daily activities, organic dust is present in these occupational environments, creating the optimal conditions for occupational exposure by the inhalation route. This study was employed a review method regarding the fungal exposure in agricultural environments reported between 2000 and 2019. The exclusive use of active sampling was found in 10 out of the 18 studies and the most common assay was the culture based-methods allowing morphological identification. Aspergillus was the most common genera found, while Alternaria alternata was the species more frequently described. This study raises concerns about occupational exposure to fungi on agriculture environments due to the high concentrations of organic dust and highlights the importance to use more than one sampling and assay methods to have an accurate exposure assessment.